2018
DOI: 10.20950/1678-2305.2018.44.4.373
|View full text |Cite
|
Sign up to set email alerts
|

SOBRE A ALIMENTAÇÃO DE LARVAS DO CAMARÃO DE ÁGUA DOCE Macrobrachium rosembergii

Abstract: The hatchery of Macrobrachium rosenbergii is a successful activity that supports freshwater prawn farming operations worldwide, although feeding schedules require improvement. As M. rosenbergii is assumed to forage at night, Artemia nauplii (AN) are normally offered in the afternoon or at night. However, at present, there is neither consensus on the optimum schedule nor the amount of nauplii that should be provided daily during the larval phase. In the present study, two aspects of the provisioning of the M. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…According to El-Sayed (2002), increased feed density in water may increase feed intake, but high intake of particles may cause feed to flow rapidly through the intestine, resulting in poor digestion and poor assimilation of nutrients hence the poor growth perfomance observed in the prawn larvae fed at high Artemia nauplii densities. These results are consistent with the study of De Aviz et al (2018), who noted that the survival rate of M. rosenbergii decreased when Artemia nauplii density increased from 5 to 10 and 20 nauplii/mL. In another study, Maciel et al (2012) observed an increase in feed intake as feed density increased, but this did not lead to an increase in yield.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to El-Sayed (2002), increased feed density in water may increase feed intake, but high intake of particles may cause feed to flow rapidly through the intestine, resulting in poor digestion and poor assimilation of nutrients hence the poor growth perfomance observed in the prawn larvae fed at high Artemia nauplii densities. These results are consistent with the study of De Aviz et al (2018), who noted that the survival rate of M. rosenbergii decreased when Artemia nauplii density increased from 5 to 10 and 20 nauplii/mL. In another study, Maciel et al (2012) observed an increase in feed intake as feed density increased, but this did not lead to an increase in yield.…”
Section: Discussionsupporting
confidence: 91%
“…Artemia nauplii remain the most essential food for marine crustacean larvae and fish due to their nutritional quality, digestibility, ability to combine the benefits of live and dry diets, and convenience of dry cysts that can hatch within 24 h (Bardócz et al, 1999;Nkambo et al, 2019;Van Stappen et al, 2020). Although Artemia nauplii have been widely used in other freshwater prawn larval culture (Kovalenko et al, 2002;Barros and Valenti, 2003;De Aviz et al, 2018), their use in larval rearing of M. rude larvae has not been documented. In addition, optimal feeding density of Artemia nauplii is essential for the survival of M. rude and avoid overfeeding, which can lead to poor water quality, high costs of tank cleaning and maintenance, and stress on larvae (De Aviz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wei et al, 2021) Feed They concluded to feed during daylight with Artemia nauplii up to 5 not exceeding 10 mL 1 . (Aviz et al, 2018) They evaluated of semi-moist product with squid (Santos-Gutiérrez et al, 2011) production (Levy et al, 2017;Malecha, 2012), given the feasibility with which they can be managed at high densities and homogeneous sizes. Some commercial hatcheries (such as the prawn biotechnology company Enzootic) have developed high-density monosex female technology for selective breeding.…”
Section: Conditions For the Larval Rearing Contribution Referencementioning
confidence: 99%
“…Knowledge of feeding behavior is necessary to determine appropriate food management for a particular organism (Loya-Javellana, 1989;Sorgeloos and Léger, 1992;Lavens and Sorgeloos, 2000;Aviz et al, 2018). The larvae of M. carcinus are small and extremely fragile during early developmental stages when they are passing through various phases with quite different morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%